Successful emergent coil embolization of an inferior epigastric artery perforation in a neonate. Issue 4 (October 2016) - Kojima, Takuro; Yoshiba, Shigeki; Kobayashi, Toshiki; Kumamoto, Takashi; Cho, Ami; Yasuhara, Jun; Shimizu, Hiroyuki; Sumitomo, Naokata
Abstract: A 28-day-old neonate with a postoperative ventricular septal defect and coarctation of aorta suffered from a right inferior epigastric artery perforation at the time of a central venous catheter placement. It resulted in a rapid and extreme hemoglobin decrease and decrease in the systolic blood pressure. The contrast computed tomography scan revealed a large amount of retroperitoneal hemorrhaging and a hematoma. Pressure hemostasis was not effective in eliminating the extravasation and surgical hemostasis seemed uncertain to succeed, because the baby was too small and its condition was unstable. An emergent coil embolization using a Target ® coil (Stryker Inc., Tokyo, Japan) was effective in completely eliminating the extravasation, resulting in saving its life. We speculated that a coil embolization was the only solution to rescue a neonate with a retroperitoneal hemorrhage due to an artery perforation. <Learning objective: Retroperitoneal hemorrhaging caused by an inferior epigastric artery perforation is a fatal condition in a neonate, because the neonate cannot express symptoms and this results in a delay in diagnosing it. Pressure hemostasis and surgical hemostasis are not effective in these cases. If a peritoneal hemorrhage is suspected, a coil embolization must be performed promptly as a sole solution to rescue the patient.>